Effect of Arthrospira maxima and Chlorella vulgaris to Lipid Profile and Visceral Fat Index Alteration in Streptozotocin-Induced Hyperglycemia Rats - Mulyati Mulyati; Aprilia Rahmawati; Slamet Widiyanto (Universitas Gadjah Mada, 2020)
Arthrospira maxima and Chlorella vulgaris contain protein, carbohydrates, antioxidants, omega-3 fatty acids, and many micronutrients. Those compounds have potency of antidiabetic and hypolipidemic activity. This study aimed to evaluate the effect of A. maxima and C. vulgaris powder administration on alteration of body weight, lipid profile, glucose levels, and visceral fat index of hyperglycemia rats. Twenty male rats were divided into 5 groups i.e. negative control (NC), hyperglycemia control (HC), metformin (M), A. maxima (AR), and C. vulgaris (CH). Body weight and visceral fat index were measured and calculated by semianalytic and analytical scales. Serum glucose levels were measured by Easy Touch GCU (Glucose, Cholesterol, Uric acid). Lipid profile levels were measured using the photometric enzymatic method. The results showed no differences in body weight between groups, except in AR group was found significantly decreased in body weight on the 20th day. Glucose serum, total cholesterol, HDL and triglyceride levels in microalgae treatment groups were not significantly different be compare to control group. LDL levels of D30 significantly different from D0, but neither between groups. The visceral fat index of a control group was higher compared to that of a microalgae group and significantly different. In conclusion, the administration of microalgae A. maxima and C. vulgaris for 30 days are effective to reduce visceral fat index but not effective to maintain body weight, glucose level, as well as not effective to improve lipid profile.